2018
DOI: 10.24136/eq.2018.004
|View full text |Cite
|
Sign up to set email alerts
|

Local determinants of foreign direct investment in Poland: the role of relative distance

Abstract: Research background: The increasing role of foreign direct investments (FDI) in global, national, regional, and local economies draws the public’s attention to the criteria utilised by foreign investors in undertaking locational decisions, owing to the mostly stimulating character of these kinds of investments.  Purpose of the article: The aim of the article is to identify the local determinants of FDI distribution. Particular attention is put on the role of distance to: (i) various transport endowments;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
2
12
0
1
Order By: Relevance
“…In many studies on the spatial distribution of the FDI (Cieślik 2005a(Cieślik , 2005b(Cieślik , 2013Holl and Mariotti 2018;Li et al 2017;Nazarczuk and Krajewska 2018;Piperopoulos et al 2018;Schäffler et al 2016), a Poisson and/or negative binomial approaches are utilised. Due to the presence of overdispersion, the negative binomial (NB) model is the preferred choice.…”
Section: )mentioning
confidence: 99%
“…In many studies on the spatial distribution of the FDI (Cieślik 2005a(Cieślik , 2005b(Cieślik , 2013Holl and Mariotti 2018;Li et al 2017;Nazarczuk and Krajewska 2018;Piperopoulos et al 2018;Schäffler et al 2016), a Poisson and/or negative binomial approaches are utilised. Due to the presence of overdispersion, the negative binomial (NB) model is the preferred choice.…”
Section: )mentioning
confidence: 99%
“…For the rest of the Polish regions, geographical factors and efficiency are the main drivers of FDI. In a recent study, Nazarczuk and Krajewska (2017) showed the importance of geographical factors and structural characteristics in attracting FDI in Polish districts in the period 2011-2015. Using negative binomial regression models, the authors showed that FDI was mostly located in Polish districts near large urban centers with high economic and social development reflected in the quality of human resources, access on labor market and infrastructure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Investments are observed as factors of the technical and technological production renovation, structural shifts in the national economy, an increase in the economic qualitative indicators at the micro and macro levels, a guarantee of a country's macroeconomic stability (Rahimi, 2016;Damoska Sekuloska, 2018;Nazarczuk & Krajewska, 2018;Do & Park, 2018;Špička, 2018). The formation of the country's favorable investment environment, being under the influence of external and internal factors, is considered to be the basis for investment attractiveness of any country (Cheba & Szopik-Depczyńska, 2017).…”
Section: Introductionmentioning
confidence: 99%